Scientific production on Environmental, Social, and Governance issues and the Sustainable Development Goals in universities - Barros, Thiago Antonio Beuron Corrêa de; Bizerril, Marcelo Ximenes Aguiar; Schvartz, Marceli Adriane; Ávila, Lucas Veiga (Revista de administração da UFSM, 2025)
Purpose: This article analyzes the academic production related to sustainable development and governance initiatives for sustainability in universities, focusing on environmental, social, and governance (ESG) issues and the sustainable development goals (SDGs).Methodology: A systematic literature review was conducted using the Web of Science database, covering publications from the last five years (2019-2024). The search utilized terms related to ESG and SDGs as keywords.Results: The article offers insights into the most current approaches and research agendas concerning ESG and SDGs in universities. Additionally, it examines the integration of Brazilian research within the global context, highlighting the main trends and theoretical contributions on this subject. Social and practical implications: The study can guide the formulation of policies and strategies in universities aiming to integrate ESG and SDGs into their operations and research activities. Originality: It contributes to the conceptual and theoretical field by mapping publications on ESG and SDGs in universities, employing a systematic approach to understanding trends and gaps in current literature. It underscores the position of Brazilian research in the international scenario of sustainable development within the academic context.